Significance of commissural calcification on outcome of mitral balloon valvotomy - Sutaria, N (2000)
OBJECTIVE—To evaluate the significance of commissural calcification, identified by transthoracic echocardiography, on the haemodynamic and symptomatic outcome of mitral balloon valvotomy. METHODS—Commissural calcification was graded from 0-4 using parasternal short axis transthoracic views. The morphology of the mitral valve was also assessed using the Massachusetts General Hospital echo score. SETTING—A tertiary cardiac centre in Scotland. PATIENTS—300 patients were studied, 85 retrospectively and 215 prospectively. Mean (SD) age was 59.8 (12.7) years, range 13 to 87; 30% had been judged unsuitable for surgery. Median echo score was 6.8 (3.0), range 2-16. MAIN OUTCOME MEASURES—Immediate increase in mitral valve area and in New York Heart Association functional class 1-3 months after balloon valvotomy. RESULTS—On univariate and multivariate analysis, commissural calcification grade was a significant predictor of achieving a mitral valve area of > 1.50 cm(2) without severe mitral reflux. Its influence was greatest in patients with an echo score ⩽ 8: those with commissural calcification grade 0/1 had significantly greater improvement in valve area and symptom status than those with grade 2/3; the proportions of patients achieving a final valve area of > 1.50 cm(2) were 67% and 46%, respectively (p < 0.05). In patients with an echo score of > 8, the influence of commissural calcification was smaller and not significant. CONCLUSIONS—Commissural calcification as assessed by transthoracic echocardiography is a useful predictor of outcome in patients with otherwise "good" valves (echo score ⩽ 8). Calcification of one commissure or more predicts a less than 50% probability of achieving a valve area above 1.50 cm(2) and is an indication for valve replacement in those who are suitable for surgery.   Keywords: mitral balloon valvotomy; commissure calcification